2014
DOI: 10.1111/are.12442
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relatedness and differentiation of hatchery populations of Asian seabass (Lates calcarifer) (Bloch, 1790) broodstock in Thailand inferred from microsatellite genetic markers

Abstract: After more than 20 years of hatchery production of Asian seabass in Thailand, genetic information is still lacking for effective genetic management and a selective breeding programme. This study aimed to evaluate genetic status of existing hatchery populations and genetic consequences of a selective breeding attempt. We examined genetic relatedness in seven hatchery samples, including a selectively bred population (RACF-F1), compared with three wild samples using 11 microsatellite loci. Genetic diversity and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…). According to the results from Senanan, Pechsiri, Sonkaew, Na‐Nakorn, Sean‐In and Yashiro () and Yue, Zhu, Lo, Wang, Lin, Feng, Pang, Li, Gong, Liu, Tan, Chou, Lim and Orban (), captive stocks from Southeast Asia displayed higher levels of allelic genetic diversity when compared to the Australian populations presented in this study. This could be due to differences in the evolutionary history of regional populations, sample size or the use of different genetic markers by our studies.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…). According to the results from Senanan, Pechsiri, Sonkaew, Na‐Nakorn, Sean‐In and Yashiro () and Yue, Zhu, Lo, Wang, Lin, Feng, Pang, Li, Gong, Liu, Tan, Chou, Lim and Orban (), captive stocks from Southeast Asia displayed higher levels of allelic genetic diversity when compared to the Australian populations presented in this study. This could be due to differences in the evolutionary history of regional populations, sample size or the use of different genetic markers by our studies.…”
Section: Discussionsupporting
confidence: 50%
“…This could be due to differences in the evolutionary history of regional populations, sample size or the use of different genetic markers by our studies. Three of the loci used in our study were also utilized by Senanan et al (2014), and 10 loci were used by Yue et al (2009). Previous DNA barcoding analysis has revealed that Australian and Myanmar barramundi samples might represent two different species (Ward, Holmes & Yearsley 2008), and this could also account for the observed differences between this study and those of individuals from Southeast Asia.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Asian seabass or also known as barramundi or giant sea perch ( Lates calcarifer Bloch) is an economically important catadromous fish species in Asia Pacific region and Australia. Thailand has been one of the major producers of fingerlings and marketable fish for both domestic and regional markets, including China, Taiwan, Indonesia, Malaysia and Singapore (Joerakate et al, ; Senanan et al, ). The production of Asian seabass has emerged as one of the fastest‐growing sectors in the global aquaculture industry with recent market expansion growth in many European and North American countries (Glencross, Blyth, Irvin, Bourne, & Wade, ; Harrison, Calogeras, & Phillips, ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the factors that influences the genetic variability of farm stocks and represents the first step in any improvement program is the formation of the broodstock (Fernández, Toro, Sonesson, & Villanueva, ; Hayes, He, Moen, & Bennewitz, ; Holtsmark, Klemetsdal, Sonesson, & Woolliams, ; Senanan, Pechsiri, Sonkaew, Na‐nakorn, & Sean‐in, ). The original broodstock of C. macropomum was established in 1966 in the Rodolfo von Ihering Agricultural Research Centre (CPaq) in the town of Pentecostes, in the Brazilian state of Ceará.…”
Section: Introductionmentioning
confidence: 99%